2023
DOI: 10.1109/tnsre.2023.3241649
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Task Irrelevant Distractions Enhance the Detection of Attention Deficit/Hyperactivity Disorder

Abstract: Early diagnosis and treatment can reduce the symptoms of Attention Deficit/Hyperactivity Disorder (ADHD) in children, but medical diagnosis is usually delayed. Hence, it is important to increase the efficiency of early diagnosis. Previous studies used behavioral and neuronal data during GO/NOGO task to help detect ADHD and the accuracy differed considerably from 53% to 92%, depending on the employed methods and the number of electroencephalogram (EEG) channels. It remains unclear whether data from a few EEG ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…To further investigate the impact of bacterial growth on EEG signals, we applied several ML classifiers to separate datasets given the experimental manipulations. As EEG data are complex, many studies have confirmed that ML methods can be used to analyze EEG signals in a multivariate fashion for assisting in the diagnosis of brain disorders [50][51][52] . In this study, we employed ML methods to separate the datasets of each manipulation with an accuracy greater than 88%, confirming the alternating effects of experimental manipulations on brain signals, despite the paired t-test being unable to find a significant difference between glycerol and water.…”
Section: Classifiers To Verify the Effect Of Manipulations On Eeg Act...mentioning
confidence: 99%
“…To further investigate the impact of bacterial growth on EEG signals, we applied several ML classifiers to separate datasets given the experimental manipulations. As EEG data are complex, many studies have confirmed that ML methods can be used to analyze EEG signals in a multivariate fashion for assisting in the diagnosis of brain disorders [50][51][52] . In this study, we employed ML methods to separate the datasets of each manipulation with an accuracy greater than 88%, confirming the alternating effects of experimental manipulations on brain signals, despite the paired t-test being unable to find a significant difference between glycerol and water.…”
Section: Classifiers To Verify the Effect Of Manipulations On Eeg Act...mentioning
confidence: 99%